Evaluasi Mutu Fisik dan Uji Hedonik Krim Minyak Cendana (Santalum album L.) sebagai Antiinflamasi - Ni Made Dharma Shantini Suena; Ni Luh Wayan Mudia Ariani; Ni Putu Udayana Antari (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2022)
Inflammation is the body's defense response used to fight agents that cause cell damage in an organism. One source of natural ingredients whose content can be developed as an anti-inflammatory with low side effects is Sandalwood (Santalum album L.). The pharmaceutical preparation chosen for the development of Sandalwood oil as an anti-inflammatory is a cream, because of its several advantages, namely, it is more convenient, practical, easy to use, not sticky, and easy to wash with water so it is easy to clean. The purpose of this study was to determine the physical quality of sandalwood oil cream using two variant concentrations of surfactant sodium lauryl sulfate 1.5% (F1) and 2.5% (F2) as an emulsifying agent, as well as to determine consumer perceptions of sandalwood oil cream. In ensuring pharmaceutical quality, the preparations made must meet several physical parameters including organoleptic tests, homogeneity tests, pH tests, mechanical stability tests, dispersibility tests, and hedonic tests. To find out whether there is a significant difference between F1 and F2, statistical data processing of cream physical quality was performed using SPSS 20 with an unpaired T-test if the data were normally distributed, and if the data were not normally distributed, the Mann-Whitney test was performed. The results of the research that has been carried out show that overall the two cream formulas have good physical quality and are quite liked by the panelists. From the results of the organoleptic test, homogeneity test, and pH test, it is known that F1 and F2 have no difference, and the results of the dispersion test and hedonic test show that there is no significant difference between F1 and F2.